Elucidating the origin of electroplasticity in metallic materials. (December 2020) - Kim, Moon-Jo; Yoon, Sangmoon; Park, Siwook; Jeong, Hye-Jin; Park, Ju-Won; Kim, Kuntae; Jo, Janghyun; Heo, Taehoon; Hong, Sung-Tae; Cho, Seung Hyun; Kwon, Young-Kyun; Choi, In-Suk; et al.
Highlights: The origin of electroplasticity in metallic materials is elucidated. From first principle calculation, a charge imbalance near defects can weaken atomic bonding under electric current. The electroplastic deformation under electric current can be well described by the FE simulation that incorporated the athermal effect of electroplasticity. The weakening of atomic bonding was also confirmed by measuring the elastic modulus under electric current. The electroplastic phenomenon could be explained by the weakening of atomic bonding due to a charge imbalance near defects under electric current. Abstract: Electroplastic phenomenon has been demonstrated by that the elongation increases remarkably during deformation under electric current without a significant elevation of temperature due to Joule heating. Since the 1960s, the electroplasticity has been actively investigated; however, an exact explanation of the mechanism has been lacking. In this study, the origin of electroplasticity in metallic materials is elucidated based on first principle calculation, finite element simulation and experimental approaches. First principle calculations on a system that includes a grain boundary, which is the general defect in polycrystalline metallic materials, show that a charge imbalance near defects weakens drastically atomic bonding under electric current. The electroplastic behavior could be well reproduced with a small-scale, microstructure-based finite element simulation, which incorporates an effective temperature near defects under electric current. The effective temperature under electric current reflects the weakening of atomic bonding due to charge imbalance. In addition, the weakening of atomic bonding was confirmed by measuring the elastic modulus under electric current, which is inherently related to the atomic bonding strength. It can be said that the mechanical properties under electric current ultimately depend on the existing defects in metallic materials. Graphical abstract: Image, graphical abstract